Pendampingan Usaha Mikro: Peran Pemasaran Digital dalam Meningkatkan Penjualan Produk Perawatan Rambut - Hadassah Ely Sharon; Hansen Hanjaya; Gita Noviani; Angeline Vanly Susanto; Steffie Adrienne Wikhova; Halim Prayogo; Angeline Shanice Tanaya; Rouvin Lim; Eko Suhartanto (Universitas Serang Raya, 2024)
Micro, small and medium enterprises are an economic force through their ability to absorb labor. One of the business categories that has great opportunities is beauty services because the number is still small in Tasikmalaya. The Covid-19 pandemic is the main obstacle forcing businesses to market their products/services conventionally. Talita Care is a beauty businesses that use conventional marketing. It does not have sufficient skills in doing Pemasaran Digital. This mentoring program aims to develop Talita Care capabilities, especially in Pemasaran Digital. The paper focuses on the application of Pemasaran Digital in Talita Care due to its potential abilities to help Talita Care reach its consumer, even after the pandemic is over. Given the pandemic conditions, the mentoring program is carried out online using Zoom media. This program has succeeded in providing new marketing channels, increasing sales through digital platforms and increasing for Talita Care owner's hard skills in Pemasaran Digital.